Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.11124/jbisrir-2016-003301
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of rifampicin chemoprophylaxis in preventing leprosy in patient contacts: a systematic review of quantitative and qualitative evidence

Abstract: Chemoprophylaxis with one dose of rifampicin is found to be effective in preventing contacts of leprosy patients from contracting the disease. Also, there is indication that this strategy is socially accepted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 37 publications
1
15
0
1
Order By: Relevance
“…Contact tracing and geographic information systems studies reveal a concentration of new patients among household and social contacts, either children or adults, of previous patients highlighting the importance of developing differentiated actions for surveillance of this group 19 21 . Simulation studies 22 and systematic reviews 23 suggest that the control of leprosy could be achieved faster through household contact tracing associated with new interventions such as chemo or immunoprophylactic approaches 17 , 18 , 24 . Indeed, immunoprophylaxis and contact surveillance has an impact on outcome 17 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Contact tracing and geographic information systems studies reveal a concentration of new patients among household and social contacts, either children or adults, of previous patients highlighting the importance of developing differentiated actions for surveillance of this group 19 21 . Simulation studies 22 and systematic reviews 23 suggest that the control of leprosy could be achieved faster through household contact tracing associated with new interventions such as chemo or immunoprophylactic approaches 17 , 18 , 24 . Indeed, immunoprophylaxis and contact surveillance has an impact on outcome 17 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Two additional systematic reviews of quantitative and qualitative data and a meta-analysis in 2017 and 2018 confirmed the effectiveness of SDR as PEP and the general acceptance of the approach. 142,143 Preventive chemotherapy has become part of leprosy control. This is needed, since the incidence has been more or less stable at around 210,000 in the past 10 years.…”
Section: Chemoprophylaxismentioning
confidence: 99%
“…Another systematic review showed that one dose of rifampicin reduced the incidence of leprosy among contacts of leprosy patients in the first two years by 56.5% and that this intervention is socially accepted. 15 Individually, BCG vaccination and chemoprophylaxis have been shown to be effective strategies in preventing leprosy. A study, which assessed the combined effect of BCG vaccination and single dose rifampicin on leprosy prevention, showed that the protective effects provided by BCG vaccination and rifampicin, independently, were 57% and 58%, respectively.…”
Section: Introductionmentioning
confidence: 99%